(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
The rewriting of the Theban myth as a monologue, Jocaste, by the Belgian writer Michèle Fabien creates an empathic relationship with the audience in which the actress’ body (key presence rather than representation) and her voice (conveying the phatic function which creates the theatre community) are involved. After being abandoned at the time of her suicide while the witnesses’ attention was focused on Oedipus (in Sophocles), deprived throughout the centuries of a gaze revealing her intimate drama, Jocasta begs Ersatz and demands that the Spectator keeps on looking. The audience, closed within a constraining set, takes part in a triple event: a trial (he/she is accused of centuries-old blindness), a psychoanalytic session (his/her presence guarantees the efficacy of Jocasta’s words), and an erotic encounter (a theatre performance has the same privileges as a love relationship: freedom from any form of finiteness, gratuity, ignorance of any time sequence).